Avaliação da eficácia de antígenos vacinais contra a infecção de Trypanosoma cruzi, em camundongos C57BL/6 α1,3-galactosiltransferase knockout - Gisele Macêdo Rodrigues da Cunha (2020)
To date, there are no vaccines available for prevention or that contribute to the treatment of Chagas disease in humans. Thus, we seek to evaluate the effectiveness of selected peptides from surface proteins: TS and MASP, from the α-Gal epitope and their associations (TS/ MASP, TS/α-Gal, MASP/α-Gal and TS/MASP/α -Gal), coupled with Qβ-VLP, as vaccine antigens against infection by Trypanosoma cruzi, in C57BL/6 α1,3galactosyltransferase knockout mice. These peptides have epitopes that are recognized by CD4+ and CD8+ memory T lymphocytes. Whereas the α-Gal epitope can induce a strong activation of the B lymphocyte-mediated response. Therefore, the association of these vaccine antigens can probably provide resistance to the host. Since studies have already shown that the control of the spread of T. cruzi is associated with the simultaneous activation of both types of adaptive response. For this work, adult female mice (5-10), who received 3 doses of vaccine antigens and their associations, were inoculated with the Y or Colombiana strain. The effect of vaccinations on the evolution of the infection was assessed through the levels of parasitism in peripheral blood and cardiac tissues, variations in initial body mass and survivability. The efficacy of vaccinations in preventing cardiac tissue damage associated with infection was assessed through semi-quantitative histopathological analysis of cell infiltrate, degenerative changes, and hypertrophy of muscle fibers in the heart. The levels of total IgG antibodies and cytokines IL-12p40, IFN-γ, IL-4 and IL-10 were measured during infection, to assess the adaptive immune response. Our results demonstrated that these antigens and their associations are probably capable of inducing the development of an effective immune response that caused the reduction of the parasitic load in the blood and inflammation in the cardiac tissues during the chronic phase, which consequently will result in less damage to the heart, providing resistance to the host. However, these vaccine targets showed different degrees of protection against T. cruzi infection, where the association Qβ-TS/MASP/α-Gal demonstrated a better performance. These results reinforce the idea that the association of antigens capable of inducing the activation of the adaptive immune response, mediated both by T lymphocytes (such as TS and MASP peptides) and by B lymphocytes (such as the α-Gal epitope), can probably be more effective in providing resistance to T. cruzi infection.